Pengenalan Konsep Gejala Alam pada Anak di TK Anugerah Mapoli Kota Kupang - Fernando Saragih; Bella Theo Tomi Pamungkas (Universitas Nusa Cendana, 2022)
Natural phenomena are conditions or situations strongly influenced by natural conditions. These conditions or situations can be in the form of disasters or non-natural disasters. Introducing the concept of natural phenomena is one of the effective steps in introducing nature to children. This introduction can be done through friendly learning according to the age and characteristics of the child. In the process, children can be introduced to some natural phenomena that often occur in their environment. This learning can be carried out through outreach activities in PKM activities. This activity was carried out at KB Kurnia Bakunase, Kupang City. Topographically, Kupang City consists of low-lying areas, coastal areas, and hills, which, based on its location; Kupang City is an area that is prone to earthquakes, tsunamis, floods and droughts. Based on this, we should introduce some natural phenomena in the area where the child lives so that the children can immediately understand the concept of natural phenomena around them.